Analyzing the influence of Shopee and Tiktok live shopping discounts on consumer spending patterns - Utomo, Jihan Husnia; Kanedi, Fidela Jovita; Sholihah, Annisa Mufidatun; Pramesty, Nabilla Sabta Putri; Rakhmawati, Nur Aini (Marketing Management Studies, 2023)
The economic growth of Indonesia and increased internet usage have contributed to a 33.5% surge in online shopping. Popular platforms such as TikTok and Shopee offer live shopping features and discounts. This research aims to explore the impact of live shopping discounts from Shopee and TikTok on consumer behavior. The research methodology involves quantitative analysis using a questionnaire and Non-Probability Sampling, specifically purposive sampling. The target respondents are TikTok and Shopee users who have made at least one purchase using discounts through live streaming. A survey was conducted with 100 respondents and analyzed using validity tests, reliability tests, correlation tests, and T-tests. The findings reveal that discounts offered during live shopping events significantly influence purchasing decisions on both platforms. The study rejects the null hypothesis (H0) and accepts the alternative hypothesis (H1), indicating the substantial influence of live shopping discounts on consumer behavior.